THE INFLUENCE OF DISCIPLINE AND WORK ENVIRONMENT ON TEACHER PERFORMANCE IN MTsN 3 BIREUEN - Ainol Mastura; Asmariatul More; Rizki Andriansyah; Muhammad Ferdiananda Chadafi; Zalikha (International Conference on Health Science, Green Economics, Educational Review and Technology, 2023)
The aim of this research is to find out how discipline and the work environment influence teacher performance at MTsN 3 Bireuen. In conducting this research the author chose a quantitative type with a survey approach. The population in this study were all teachers at MTsN 3 Bireuen, totaling 45 people. The sample in this research was all teachers at MTsN 3 Bireuen, totaling 45 people. In an effort to obtain the data needed and to support this research, the method used was the questionnaire method. The work discipline regression coefficient (X1) of 0.635 states that an increase in the work discipline variable coefficient (X1) of 1% will cause work discipline to increase by 63.5%. The work environment regression coefficient (X2) of 0.070 states that an increase in the work environment variable coefficient (X2) of 1% will cause the work environment to increase by 07.0%.